Working in a 24/7 Economy : Challenges for American Families - Presser, Harriet B. (Book collections on Project MUSE., 2003)
This book looks at the effects of nonstandard work schedules on family functioning and shows how these schedules disrupt marriages and force families to cobble together complex child-care arrangements that should concern us all. The number of hours Americans work has received ample attention, but the issue of which hours-or days-Americans work has received much less scrutiny. This work provides a comprehensive overview of who works nonstandard schedules and why. The author argues that the growth in women's employment, technological change, and other demographic changes over the past thirty years gave rise to the growing demand for late-shift and weekend employment in the service sector. It is also demonstrated that most people who work these hours do so primarily because it is a job requirement, rather than a choice based on personal considerations. The consequences of working non-standard schedules often differ for men and women since housework and child-rearing remain assigned primarily to women even when both spouses are employed. As with many other social problems, the burden of these schedules disproportionately affects the working poor, reflecting their lack of options in the workplace and adding to their disadvantage. The book shows how such work arrangements have created a new rhythm of daily life within many American families, including those with two earners and absent fathers. With spouses often not at home together in the evenings or nights, and parents often not at home with their children at such times, the relatively new concept of home-time has emerged as primary concern for families across the nation.